TRANSCULTURAL NURSING - Ahmad Sayuti, Risnah (Universitas Islam Negeri Alauddin Makassar, 2015)
Transcultural nursing is one of the main areas in nursing which focuses on comparative and analytical study on the different cultures and sub-cultures in the world that appreciates caring, nursing services, values, and health-ill belief, as well as behavior types which aims to develop scientific and humanistic body of knowledge to give a place for nursing practice of certain culture dan universal culture (Marriner-Tomey, 1994). The theory of transcultural nursing emphasizes on the necessity of nurse roles in understanding the culture of the client. The nursing role in the theory of transcultural nursing is to facilitate the nursing system conducted by the common society with the professional nursing system through nursing education. The existence of the nurse roles in transcultural nursing theory is described by Leininger. Therefore, the nurse should be able to make decision with the nursing action plan that must be given to the society.